Digital stress perception among German hospital nurses and associations with health-oriented leadership, emotional exhaustion and work-privacy conflict: a cross-sectional study - Jessica Kräft; Tanja Wirth; Volker Harth; Stefanie Mache (BMC Nursing, 2024)
Abstract Background The use of digital information and communication technologies (ICT) can be accompanied by increased technostress for nursing staff, which in turn can be associated with health consequences. In addition, the use-related constant accessibility through ICT can have a negative impact on health-related recovery and regeneration phases. Health-promoting behaviors of supervisors can influence health complaints and conflicts between employees’ work and private lives. The present study investigates whether there is a corresponding relationship between digital stressors (technostressors) as well as health-oriented leadership and health outcomes among nurses. Methods In a quantitative online survey, hospital nursing staff (n = 243) was asked about techno-invasion, social environment, emotional exhaustion, work-privacy conflict and on the supervisors’ health-oriented staff-care dimensions awareness, value of health and health-oriented leadership behavior (HoL: awareness, value of health and health behavior). The associations of technostress, HoL and health outcomes were tested using regression analyses and performing a correlation. Results Significant positive associations between techno-invasion and health outcomes had been found. Social environment was not (positively) significantly related to either emotional exhaustion or work-privacy conflict. Health-oriented leadership moderated the association between social environment and work-privacy conflict. Conclusions The results confirm the relevance of measures to reduce technostress and the importance of health-oriented leadership as a health-promoting resource. For practice, offers should be implemented for a balanced work and personal life of the nursing staff as well as establishing competence trainings for supervisors to learn and implement health-promoting behaviors. When technology use can’t be reduced, options could be created to ensure that nurses’ work and private lives become more balanced. These could represent mindfulness practices.